Prognostic Value of Beclin-1 and HIF-1α in Oral Squamous Cell Carcinoma - Radi, Nadia Attia; Habba, Doaa Adel; Hallool, Seham Ibrahim; Alqahtani, Sulaiman Saeed; Abd Elsamia, Hanaa Mohamed (European Journal of Dentistry, 2025)
Objectives Certain factors that disturb the tumor microenvironment influence the promotion of tumorigenesis. Detecting gene expression at the protein level is highly valuable and complements the histopathological analysis achieved by immunohistochemistry (IHC). Hypoxia-inducible factor (HIF)-1α accomplishes autophagy induction and regulation of autophagy-associated genes. So, this study was carried out to evaluate the tissue protein expression of Beclin-1 and HIF-1α using IHC and correlate their expression with the prognosis of oral squamous cell carcinoma (OSCC).Materials and Methods Immunohistochemical evaluation of Beclin-1 and HIF-1α was done in 5 samples of normal oral epithelial tissues and 45 samples of OSCC, which were classified histologically into 15 samples each of well, moderately, and poorly differentiated squamous cell carcinoma.Results According to statistics, normal tissue had the highest values for Beclin-1, while poorly differentiated OSCC had the lowest mean area percentage. HIF-1α showed the opposite results. These results indicate that the association of both molecules has a greater role in the transformation from normal to different histopathological grades of OSCC.Conclusion The close association between Beclin-1 and HIF-1α identified in the current study confirms hypoxia's critical role in autophagy activation. Moreover, reduced Beclin-1 and elevated HIF-1α expression were significantly associated with the histopathological grading of OSCC, supporting their pivotal role in the development and progression of OSCC.
Keywords: autophagy; Beclin-1; HIF1α; OSCC